Adequação do sistema preventivo de combate ao incêndio: estudo de caso hotel Caesar Park - Santanna, Márcio de (2010)
This essay Project aims at producing a criterion, through a methodological structure, to define a quality firefighting system to the hotel sector, using the analysis of the Caesar Park Hotel case. There are four kinds of applied methods: (i) research, selection and study of the written material about the subject; (ii) gathering and interpretation of data; (iii) qualitative research, with skilled personnel interviews in firefighting projects, particularly the Rio de Janeiro State Fire Department and specialized firms; (iv) analysis and comments of the collected data. The methodology will be demonstrated with its application to the Caesar Park Hotel